Photobiomodulation use in ophthalmology – an overview of translational research from bench to bedside - Valter, Krisztina; Tedford, Stephanie E.; Eells, Janis T.; Tedford, Clark E. (Frontiers in Ophthalmology, 2024)
Photobiomodulation (PBM) refers to the process in which wavelengths of light are absorbed by intracellular photoacceptors, resulting in the activation of signaling pathways that culminate in biological changes within the cell. PBM is the result of low-intensity light-induced reactions in the cell in contrast to thermal photoablation produced by high-intensity lasers. PBM has been effectively used in the clinic to enhance wound healing and mitigate pain and inflammation in musculoskeletal conditions, sports injury, and dental applications for many decades. In the past 20 years, experimental evidence has shown the benefit of PBM in increasing numbers of retinal and ophthalmic conditions. More recently, preclinical findings in ocular models have been translated to the clinic with promising results. This review discusses the preclinical and clinical evidence of the effects of PBM in ophthalmology and provides recommendations of the clinical use of PBM in the management of ocular conditions.